The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12957-022-02503-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a circRNA-miRNA-mRNA network based on differentially co-expressed circular RNA in gastric cancer tissue and plasma by bioinformatics analysis

Abstract: Background Increasing evidence implicates circular RNAs (circRNAs) have been involved in human cancer progression. However, the mechanism remains unclear. In this study, we identified novel circRNAs related to gastric cancer and constructed a circRNA-miRNA-mRNA network. Methods Microarray datasets GSE83521 and GSE93541 were obtained from the Gene Expression Omnibus (GEO). Then, we used computational biology to identify circRNAs that were differenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…miRNA sponging is the most well-studied mechanism of circRNA action, and circRNA competitively binds miRNA through complementary base pairing to inhibit the binding of miRNA to its target molecule, thereby regulating the expression of target Mrna. 37 This study confirmed circAPP as a gene modifier of miR-6838-5p. miR-6838-5p is involved in a series of biological processes in cancer.…”
Section: Discussionsupporting
confidence: 70%
“…miRNA sponging is the most well-studied mechanism of circRNA action, and circRNA competitively binds miRNA through complementary base pairing to inhibit the binding of miRNA to its target molecule, thereby regulating the expression of target Mrna. 37 This study confirmed circAPP as a gene modifier of miR-6838-5p. miR-6838-5p is involved in a series of biological processes in cancer.…”
Section: Discussionsupporting
confidence: 70%
“…12 Circ_0043947 is derived from the exons of breast cancer gene 1 (BRCA1) gene, and was discovered to be higher in both the tissues and serum of GC patients according to the GSE83521 and GSE93541 datasets, and might function in GC cells via circRNA-miRNA-mRNA network. 13 Here, we probed the action of circ_0043947 on GC oncogenicity.…”
Section: Introductionmentioning
confidence: 99%